PENGARUH PERUBAHAN IKLIM TERHADAP KEGIATAN WISATA BAHARI DI GILI TRAWANGAN - Kusmawan, Anang Taofik (JURNAL NASIONAL PARIWISATA, 2013)
A primary issue is the extent to which research and knowledge insight tourists, tourism entrepreneurs and the general public to the phenomenon of climate change. The purpose of the study was to explain the extent of knowledge of the tourists, communities, and tourism entrepreneurs on climate change and what is being done to overcome or minimize the impact of climate change, which has an influence on the tourism industry in Gili Trawangan.This qualitative descriptive study describes and illustrates the environmental conditions Gili Trawangan. The unit of analysis is a preliminary understanding on climate change experienced by tourists, community and tourism businesses, as well as the impact experienced. The results showed a lack of understanding about climate change among tourists, community and tourism businesses. A concern that arises is the damage to the environment and society Gili Trawangan declining income from tourism. Necessary action to respond to climate change between the community and tourism businesses in Gili Trawangan.